2021
DOI: 10.1002/ijc.33495
|View full text |Cite
|
Sign up to set email alerts
|

Early response by MR imaging and ultrasound as predictor of pathologic complete response to 12‐week neoadjuvant therapy for different early breast cancer subtypes: Combined analysis from the WSG ADAPT subtrials

Abstract: We evaluated the role of early response after 3 weeks of neoadjuvant treatment (NAT) assessed by ultrasound (US), magnetic resonance imaging (MRI) and Ki‐67 dynamics for prediction of pathologic complete response (pCR) in different early breast cancer subtypes. Patients with HR+/HER2+, HR−/HER2− and HR−/HER2+ tumors enrolled into three neoadjuvant WSG ADAPT subtrials underwent US, MRI and Ki‐67 assessment at diagnosis and after 3 weeks of NAT. Early response was defined as complete or partial response (US, MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Studies examining the early predictive ability of MRI have found greater accuracy compared with other imaging methods in predictive performance across breast cancer subtypes. 15 For early response prediction, functional characteristics can add information to measurements of tumor dimensions alone. A multitude of measurement methods, including radiomics approaches, can be used to quantify tumor properties.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…Studies examining the early predictive ability of MRI have found greater accuracy compared with other imaging methods in predictive performance across breast cancer subtypes. 15 For early response prediction, functional characteristics can add information to measurements of tumor dimensions alone. A multitude of measurement methods, including radiomics approaches, can be used to quantify tumor properties.…”
Section: Practical Applicationsmentioning
confidence: 99%
“…However, current monitoring methods, such as imaging technologies (e.g., ultrasound and magnetic resonance imaging [MRI]), traditional serum biomarkers (e.g., CA15-3 and CEA), and core-needle biopsy with Ki67 assay during the NAC, cannot meet the need to measure the dynamic response in NAC accurately. 3 …”
mentioning
confidence: 99%